The effect of sodium hypochlorite and ginger extract on microorganisms and endotoxins in endodontic treatment of infected root canals - Valera, Marcia Carneiro [UNESP]; Maekawa, Lilian Eiko; Chung, Adriana; Cardoso, Flavia Goulart Rosa; De Oliveira, Luciane Dias; De Oliveira, Carolina Lima; Carvalho, Claudio Antonio Talge (My University, 2014)
This in vitro study sought to evaluate the biomechanical preparation action on microorganisms and endotoxins by using sodium hypochlorite (NaOCl) and an intracanal medication containing Zingiber officinale, with or without calcium hydroxide. Single-rooted teeth were contaminated, and root canal instrumentation (using 2.5% NaOCl) was performed. Samples were divided into 4 groups, according to the intracanal medication employed. The root canal content was gathered 28 days after contamination (baseline), immediately after biomechanical preparation, 7 days after biomechanical preparation, 14 days after intracanal medication, and 7 days after intracanal medication was removed. The results (submitted to Kruskal-Wallis and Dunn tests) showed that the NaOCl eliminated 100% of root canal microorganisms and reduced 88.8% of endotoxins immediately after biomechanical preparation, and 83.2% at 7 days after biomechanical preparation.
Keywords: Calcium hydroxide; Endotoxins; Microorganisms; Sodium hypochlorite; Zingiber officinale